Private Investment Decision-making, Foreign Direct Investment Nexus: A Way Forward to Promote Sustainable Economic Growth in Pakistan - Mouneer, Salma; Ali, Hina; Hassan, Mahmood ul; Naseer, Sohail (Pakistan Journal of Humanities and Social Sciences, 2023)
This study emphasizes the importance of private investment in the economy of Pakistan. Pakistan's economy decreased daily due to less development in the foreign and trade sector. This study utilized time series data from the period 1982 to 2020. Additionally, the researcher examined the ARDL bound testing Method for the empirical analysis of the data under consideration. The data set has been collected from the State Bank of Pakistan, the Economic Survey, and the Handbook of Statistics. This study integrates private investment as the dependent variable and gross domestic product, domestic saving, foreign direct investment, indirect taxes, subsidies, and terms of trade as the independent variable. The analysis of this study showed that the gross domestic product and subsidies have a positive and insignificant impact on private investment, and Terms of Trade and Indirect Taxes have a negative and significant effect. In contrast, foreign direct investment has a positive but significant impact on private investment, and domestic saving has a positive and significant impact on private investment. The main purpose of this study is to ensure that the economy of Pakistan is maintained if the structural condition, political stability, and Government interference should be applied.